Unusual Namibian fairy circle patterns in heterogeneous and atypical environments. (May 2019) - Getzin, Stephan; Yizhaq, Hezi
Abstract: Under homogeneous habitat conditions, fairy circles are extremely ordered grassland gaps that are densely packed and that function as an extra source of water for the surrounding matrix vegetation. While the origin of fairy circles is still disputed, most of the research has so far focused on such typical habitat conditions where the fairy circles are almost round and have a grid-like hexagonal pattern. However, Namibian fairy circles also occur under atypical habitat conditions where topographical heterogeneity or extreme aridity are forcing the circles to change their shapes and patterns. In this pilot study, we are describing some striking and new examples how shapes and patterns of fairy circles may change under such atypical environmental conditions. We emphasize the need to study fairy circles in disturbed catchment areas, mega circles in drainage lines, as well as soil-water budgets of irregularly spaced fairy circles in very arid locations. Furthermore, there is need to understand the formation of the very large mega circles and desertification fronts in flat habitat. Finally, we also discuss the potential role of abiotic drivers such as soil-crust formation in the vegetation matrix or aeolian erosion and subsequent de-rooting of grasses in forming unusual fairy circle shapes, sizes and patterns. Graphical abstract: Image 1 Highlights: Fairy circles in Namibia have not yet been studied in heterogeneous environments. In such atypical habitats they may change their patterns, density, size, and shape. Understanding the abiotic drivers of these pattern changes is a research challenge.